Explorations of object and location memory using fMRI - Passaro, Antony D.; Elmore, Lauren C.; Ellmore, Timothy M.; Leising, Kenneth; Papanicolaou, Andrew C.; Wright, Anthony A. (Frontiers in Behavioral Neuroscience, 2013)
Content-specific sub-systems of visual working memory (VWM) have been explored in many neuroimaging studies with inconsistent findings and procedures across experiments. The present study employed functional magnetic resonance imaging (fMRI) and a change detection task using a high number of trials and matched stimulus displays across object and location change ("what" vs "where") conditions. Furthermore, individual task periods were studied independently across conditions to identify period-specific differences. Importantly, this combination of task controls has not previously been described in the fMRI literature. Composite results revealed differential frontoparietal activation during each task period. A separation of object and location conditions yielded a distributed system of dorsal and ventral streams during the encoding of information corresponding to bilateral inferior parietal lobule (IPL) and lingual gyrus activation, respectively. Differential activity was also shown during the maintenance of information in middle frontal structures bilaterally for objects and the right IPL and left insula for locations. Together, these results reflect a domain-specific dissociation spanning several cortices and task periods. Furthermore, differential activations suggest a general caudal-rostral separation corresponding to object and location memory, respectively.